The Tigers of Baluchistan - Matheson, Sylvia A.; With A New Introduction By Titus, Paul. (Karachi Oxford University Press, 1997)
An eyewitness account of how the Bugtis, one of the most primitive tribes of south-west Asia, are meeting the problems of sudden confrontation with 20th-century industrialization. The introduction discusses the "time-warp" surrounding the Bugtis and the whole of Baluchistan.
Include Index, Glossary and Illustrstions.
Keywords: Baluchi (Southwest Asian People) -- Bugti (Pakistani People)